Sound of the Mountain Based on a Novel by Yasunari Kawabata - Naruse, Mikio; Tamai, Masao; Hara, Setsuko; Yamamura, Soh; Uehara, Ken (Eureka Video, 2006)
Adapted from a novel by Yasunari Kawabata, the first Japanese author to be awarded the Nobel Prize for Literature, "Sound of the Mountain" typifies Naruse's preferred genre of shomin-geki (films about the daily lives of ordinary people). Set in the ancient seaside town of Kamakura, Kawabata's home, "Sound of the Mountain" depicts the increasingly close relationship between a childless young woman, Kikuko (Setsuko Hara), and her father-in-law, Shingo (So Yamamura), to whom she turns as her own marriage, to the neglectful and philandering Shuichi (Ken Uehara), disintegrates. A domestic drama of rare existential insight and emotional subtlety, "Sound of the Mountain" draws on the concerns of Naruse's earlier marriage films, including "Repast" (even the pairing of stars Hara and Uehara is reprised), to offer a profoundly moving account of the complex relationship that develops between an older man and a younger woman. [Cover]
Keywords: DVD-Video